Ação Intelectual de Theobaldo Miranda Santos no Campo Educacional: Imprensa Periódica Católica e Produção de Manuais Didáticos (1935-1947). - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The aim of this dissertation is to analyze the action of the Catholic intellectual Theobaldo Miranda Santos in the Brazilian educational field, from 1935 to 1947. It is a research situated in the scope of the History of Education, conducted more specifically from the perspective of Intellectual History. The selection and collection of sources for the survey of information took place through bibliographical and documental research. Two types of documents were used: the Catholic periodical press – namely, 2 articles in the Revista Brasileira de Pedagogia and 13 articles from the magazine A Ordem – and 4 didactical manuals from the “Coleção Atualidades Pedagógicas” – Noções de História da Educação, Noções de Psicologia Educacional, Noções de Filosofia Educacional, and Noções de Sociologia da Educação. The texts written by Miranda Santos dealt specifically with educational issues and defined the criterion of temporal delimitation in our study, that is, 1935 publication of the first article in A Ordem, and 1947 publication of the last manual in “Coleção Atualidades Pedagógicas”. As conceptual instruments for analyzing the circumscribed object for investigation, categories elaborated by the French sociologist Pierre Bourdieu were used, with emphasis on the field (educational, religious and political), social space, intellectuals, habitus, cultural capital and symbolic capital. It was verified with the investigation that Theobaldo Miranda Santos developed through his written production – athwart periodicals, and didatical manuals – an intentional action that responded to demands presented to Catholic intellectuals in relation to the Brazilian educational field. The debate with opponents of Catholic education and the didactic character of their texts were important aspects for the strengthening of Christian ideas in this field. The dialogue that Miranda Santos established with the modern pedagogical sciences was beneficial for the Brazilian Catholic Church, considering the fact of having incorporated new elements of technique and teaching practice, in order to bring renewal without disfiguring the principles that supported the traditional Catholic educational model. The wide distribution and circulation of their texts led such contents to have a reception between Catholics and non-Catholics, allowing wide access to their perspective on contents related to discussions of the Brazilian pedagogical reality, based on elements that articulated the educational, religious and political fields. It was also possible to verify that Theobaldo Miranda Santos, through his written production and his intellectual presence, managed to reach different groups in different social sectors, in order to spread the Catholic principles and propositions in education to an important number of people, with emphasis on those linked to school institutions.
Keywords: Theobaldo Miranda Santos; Intelectuais católicos; Imprensa periódica; Manuais didáticos; Campo educacional brasileiro; Theobaldo Miranda Santos; Catholic intellectuals; Periodical press; Didactical manuals; Brazilian educational field; CNPQ::CIENCIAS HUMANAS::EDUCACAO